If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -7x = 3x + -2 Reorder the terms: 3 + -7x = -2 + 3x Solving 3 + -7x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + -7x + -3x = -2 + 3x + -3x Combine like terms: -7x + -3x = -10x 3 + -10x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + -10x = -2 + 0 3 + -10x = -2 Add '-3' to each side of the equation. 3 + -3 + -10x = -2 + -3 Combine like terms: 3 + -3 = 0 0 + -10x = -2 + -3 -10x = -2 + -3 Combine like terms: -2 + -3 = -5 -10x = -5 Divide each side by '-10'. x = 0.5 Simplifying x = 0.5
| 6(2l+3)=54 | | 4-2x-1=11-4x | | 2(a-5)=28 | | 12+2y=-12+10y | | 2x-5x=1+5 | | 7y-30=9 | | iz=3+1 | | 5(x-3)+10=15 | | 3x^4-6x^3-0.16x^2=0 | | (x+2)x(x+3)=56 | | 25+X=4 | | 2(3x-1)+7=9-x | | 3xy-3yx= | | 2x-14=-2(x+3)-3 | | 3/4a=1/4 | | X=12z | | (d^3+1)y=0 | | Ix+2l=3 | | 12=4!x^(1/2) | | 12=4!x(1/2) | | 3z-5=p | | (4+8x)=10 | | 48/][587 | | 150x2/3 | | 12x+40x=572 | | 5(2x-1/25) | | cosx-(x/4)=0 | | 203=3.14*x^2 | | B=45a-7b | | cos(x)=0.5*cos(0.5*x) | | X^2-7x=-30 | | 7cosx+sinx=-5 |